Magpie - Day, Elizabeth, 1978- (New York : Simon & Schuster, 2022)
Marisa and Jake are a perfect couple. Their new lodger, Kate, and her rent payments will give them the income they need to start trying for a baby. Sure, Kate doesn't seem to care about personal boundaries and is occasionally overly familiar with Jake. But as Jake and Marisa are put through months of fertility treatments and false starts, Kate's boundary-pushing turns into an all-out obsession. Why does she seem to know everything about Marisa and Jake? In her quest to find out who Kate really is, Marisa might destroy everything she has worked so hard to create: her perfect romance, her perfect family, and her perfect self. Adapted from jacket.
"A novel. Author of THE PARTY"--Dust jacket.
"Originally published in Great Britain in 2021 by Fourth Estate"--Title page verso.
Keywords: Married people -- Fiction; Landlord and tenant -- Fiction; Infertility -- Fiction; Fertilization in vitro -- Fiction; Families -- Fiction; FICTION / Thrillers / Suspense; FICTION / Women; FICTION / Thrillers / Domestic; Families; Fertilization in vitro; Infertility; Landlord and tenant; Married people; Married people -- Fiction; Landlord and tenant -- Fiction; Infertility -- Fiction; Fertilization in vitro -- Fiction; Psychological fiction; Suspense fiction; Fictional Work; Fiction; Novels; Psychological fiction; Thrillers (Fiction); Psychological fiction; Thrillers (Fiction); Novels; Romans